Biased and inadequate, or trustworthy and sufficient? Evaluating the YouTube videos on platelet-rich plasma in orthopedics - Ayık, Gökhan; Karademir, Orhan Mete; Kolaç, Ulaş Can; Özdemir, Erdi; Huri, Gazi (Acta Medica, 2026)
Objective: Social media has transformed patient-physician interactions, with YouTube emerging as a major contributor. Platelet-rich plasma (PRP) therapy has gained substantial popularity in orthopedics despite ongoing debate regarding its effectiveness. As orthobiologic treatments are increasingly promoted directly to consumers, concerns have emerged regarding the quality, reliability, and potential bias of online information. This study aimed to evaluate the quality, reliability, and bias of YouTube videos related to PRP in orthopedics. Materials and Methods: A cross-sectional analysis of YouTube was performed, using the search terms “prp,” “prp knee,” and “prp shoulder.” The first 50 results were recorded, and after exclusions, eligible videos were analyzed. Video metadata were recorded and content sources were categorized as physician, medical institution, or non-medical sources. Information quality was assessed using Brief DISCERN instrument, JAMA Criteria, and Global Quality Score (GQS). Bias was evaluated based on predefined criteria including promotional language and testimonial-driven claims. Results: A total of 111 videos were analyzed. Physicians produced 49.5% of videos, followed by institutions (39.6%) and non-medical sources (10.8%). Overall information quality was low-to-moderate, with median Brief DISCERN, JAMA, and GQS scores of 17, 3, and 3, respectively. Significant differences were observed between uploader types for all quality metrics (DISCERN p=0.008; JAMA and GQS p<0.001). Physicians demonstrated higher quality compared to medical institutions and non-medical sources. Overall, 40.5% of videos were classified as biased, with no significant association between source and bias (p=0.0516). Non-biased videos had higher JAMA (p=0.038) and GQS (p=0.025) scores. Longer videos were associated with higher quality and engagement (all p<0.001), while popularity metrics were not associated with information quality. Conclusion: YouTube videos on PRP in orthopedics demonstrate variable quality, incomplete transparency, and a notable proportion of potentially biased content. Physician-generated content is associated with higher quality, although overall reliability and transparency remain inconsistent. These findings highlight both the need and the opportunity for more accurate, transparent, balanced, and evidence-based content to better support patient decision-making.